Stereoselective and Modular Assembly Method for Heterocycle‐Fused Daucane Sesquiterpenoids. Issue 52 (20th August 2018) - Christiaens, Mien; Hullaert, Jan; Van Hecke, Kristof; Laplace, Duchan; Winne, Johan M.
Abstract: A stereoselective synthetic method is reported for the molecular framework found in common daucane and isodaucane sesquiterpenoid natural products. The synthetic method constitutes a scalable, modular, and also asymmetric access to a complex natural product scaffold, wherein the substitution pattern and the stereochemistry can be adjusted simply by choosing different starting materials. The method allows the rapid introduction of diverse heterocyclic substructures such as (benzo)furans, (benzo)thiophenes, dithiins, thiazoles, and indoles, which actually also facilitate and direct the key intramolecular annulation step. Abstract : One, two, terpene : starting from diverse simple heterocyclic building blocks that are common drug fragments, a complex natural product carbon skeleton can be assembled in two robust synthetic operations, wherein the substitution pattern and the stereochemistry of the resulting fused polycycle can be adjusted simply by choosing different starting materials.